SOCIAL ISSUES REFLECTED IN SELECTED FILMS OF MARILOU DIAZ-ABAYA: AN ANALYSIS (March 2004) - Bautista, Florida M.; Emocling, Daisy Jane A.; and de Dios, Kristine Jem T. 4 0 16; 5
u
Thesis (Undergraduate) Pamantasan ng Lungsod ng Maynila ,2004.;Bachelor in Mass Communication.
Keywords: 2 -- 0; 6; 20; 20; 2